IBM eserver certification study guide : Cluster 1600 managed by PSSP - Quintero, Dino (IBM redbooks., 2003)
This IBM Redbooks publication is designed as a study guide for professionals wishing to prepare for the certification exam to achieve IBM Certified Specialist - Cluster 1600 managed by PSSP. The Cluster 1600 managed by PSSP certification validates the skills required to install and configure PSSP system software and to perform the administrative and diagnostic activities needed to support multiple users in an SP environment. The certification is applicable to specialists who implement and/or support Cluster 1600 managed by PSSP systems. This book helps Cluster 1600 specialists seeking a comprehensive and task-oriented guide for developing the knowledge and skills required for certification. It is designed to provide a combination of theory and practical experience needed for a general understanding of the subject matter. It also gives sample questions that will help in the evaluation of personal progress and provides familiarity with the types of questions that will be encountered in the exam.